Decentralization, decisive process and the local public politicies - Kerbauy, Maria Teresa Miceli (FCL-UNESP Laboratório Editorial, 2007)
The decisive process and the offer of new public policies in the Brazilian towns caused by the transfer of decisive responsibilities to the sub national units, established by the 1988 Brazilian Constitution, have not yet deserved a deep study by the specialists. The greatest part of the studies about those problems are focused on the analysis of the popular participation and not on the institutional process of taking decisions. This article tries to analyze those who have been elected as representatives (mayors and presidents of the municipal council) and their perception of the democratization or not of the institutional process of deciding about the public policies, having in mind the demands of the society.